Speech Prosody 2018 2018
DOI: 10.21437/speechprosody.2018-73
|View full text |Cite
|
Sign up to set email alerts
|

The acoustic fingerprint of a charismatic voice - Initial evidence from correlations between long-term spectral features and listener ratings

Abstract: What makes a charismatic speaker? The present study extends this question into the prosodic dimension of voice quality. We analyzed various F0, LTAS and LTF long-term spectral characteristics from 12 L2 speakers of English who were recorded while giving entrepreneurial speeches. The results of the acoustic analysis were correlated with indirect judgments of the entrepreneurs' charismatic performances by 98 listeners. The correlations we found replicate previous findings in that a larger F0 range and a higher/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…The study presented here is part of a larger research project aiming to investigate whether YouTubers share some of the voice characteristics of successful CEOs or politicians whose voices have been investigated in regards to their charismatic speech (e.g., [2,3,4,5,6,7]), and whether the acoustic features of the Creators in the sample correlate with some of YouTube's provided channel and video statistics: namely subscriber count, views and likes. Creators' speech is interesting for phonetic research in general and research into charismatic speech in particular because, while they are business people (they built their channels up like start-up companies over time, they have several business ventures on the side, etc.)…”
Section: Researching the Voices Of Youtube Creatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study presented here is part of a larger research project aiming to investigate whether YouTubers share some of the voice characteristics of successful CEOs or politicians whose voices have been investigated in regards to their charismatic speech (e.g., [2,3,4,5,6,7]), and whether the acoustic features of the Creators in the sample correlate with some of YouTube's provided channel and video statistics: namely subscriber count, views and likes. Creators' speech is interesting for phonetic research in general and research into charismatic speech in particular because, while they are business people (they built their channels up like start-up companies over time, they have several business ventures on the side, etc.)…”
Section: Researching the Voices Of Youtube Creatorsmentioning
confidence: 99%
“…. ] standard deviation, the greater the perceived charisma" ([2, p. 516]; see also [5] for empirical support in favour of this measure).…”
Section: Charismatic Speech and Speaker Perceptionmentioning
confidence: 99%
“…This is true even if all other factors besides gender (incl. all prosodic parameters) are equal (Novák-Tót et al, 2017;Niebuhr et al, 2018). This is rarely the case in everyday life because men's speaking skills are promoted and valued more and perhaps even judged less critically by the society than those of women (Baxter, 1999;Sellnow and Treinen, 2004;Cameron, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Phonetic studies have shown that acoustic-prosodic parameters are positively correlated with perceived speaker charisma (Strangert and Gustafson, 2008;Rosenberg and Hirschberg, 2009;Signorello et al, 2012;D'Errico et al, 2013;Niebuhr et al, 2016Niebuhr et al, , 2018. For example, higher F0 levels, larger F0 ranges, and faster speaking rates make speakers sound more charismatic.…”
Section: Introductionmentioning
confidence: 99%
“…Note that this is only a subset of all parameters that characterize the different speaking styles of Jobs and Zuckerberg and which are potentially relevant for their deviating perception in terms of persuasiveness and positive character traits. The manipulated subset was selected according to three criteria: (1) The first criterion is feasibility; for instance, differences in voice quality are very likely to have a strong impact on perceived persuasiveness and positive character traits [cf., for instance, Signorello &Demolin 2013 andNiebuhr et al 2018]. However, voice-quality parameters are hard to implement and manipulate in a consistent and natural-sounding way in stimuli with current speech-signal processing (i.e., resynthesis) tools.…”
Section: Stimulus Creationmentioning
confidence: 99%